2017
DOI: 10.3390/app7080785
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of Novel Pyrazole-Based Heterocycles as Potential Antitumor Agents

Abstract: Abstract:A new series of pyrazolylpyridines was prepared by reaction of ethyl-3-acetyl-1,5-diphenyl-1H-pyrazole-4-carboxylate with the appropriate aldehyde, malononitrile, or ethyl acetoacetate and an excess of ammonium acetate under reflux in acetic acid. Similarly, two novel bipyridine derivatives were prepared by the above reaction using terephthaldehyde in lieu of benzaldehyde derivatives. In addition, a series of 1,2,4-triazolo[4,3-a]pyrimidines was synthesized by a reaction of 6-(pyrazol-3-yl)pyrimidine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…A series of 2‐amino‐3‐cyano‐6‐(pyrazol‐3‐yl)‐pyridines 132a–f was prepared by one‐pot reaction of 3‐acetylpyrazole derivative 1 with the appropriate aldehyde 113 , malononitrile 131 , and ammonium acetate under reflux in acetic acid (Scheme ) .…”
Section: Chemistry Of 3‐acetylpyrazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of 2‐amino‐3‐cyano‐6‐(pyrazol‐3‐yl)‐pyridines 132a–f was prepared by one‐pot reaction of 3‐acetylpyrazole derivative 1 with the appropriate aldehyde 113 , malononitrile 131 , and ammonium acetate under reflux in acetic acid (Scheme ) .…”
Section: Chemistry Of 3‐acetylpyrazolesmentioning
confidence: 99%
“…In a similar manner, another series of pyrazolylpyridines 134a–f was synthesized using ethyl acetoacetate in lieu of malononitrile. Thus, reaction of 3‐acetylpyrazole derivative 1 with the appropriate aldehyde 113 , ethyl acetoacetate 133 , and ammonium acetate in refluxing acetic acid afforded the corresponding products 134a–f (Scheme ) .…”
Section: Chemistry Of 3‐acetylpyrazolesmentioning
confidence: 99%
“…A series of pyrazolylpyridines 149a – f were prepared by condensation of ethyl‐3‐acetyl‐1,5‐diphenyl‐1 H ‐pyrazole‐4‐carboxylate 147 with the appropriate aldehyde 148 , malononitrile, and an excess of ammonium acetate under reflux in acetic acid. Also, the bipyridine derivative 149g was prepared via terephthaldehyde 140f instead of benzaldehyde derivatives (Scheme ) .…”
Section: Antitumor Activitiesmentioning
confidence: 99%
“…The cytotoxicity of the pyridines 149a , 149b , and 149e derivatives was evaluated against the human liver carcinoma cell line (HEPG2‐1) using doxorubicin as a reference drug; the results revealed that the descending order of the antitumor activity of the tested compound against HEPG2‐1 cell line is as follows: 149b > 149a > 149e . The pyridine derivative 149b (IC 50 = 1.9 ± 0.16 n M ) has promising antitumor activity against HEPG2‐1 compared with doxorubicin, which is used as reference drug .…”
Section: Antitumor Activitiesmentioning
confidence: 99%
See 1 more Smart Citation